Legal protection of the consumer from manipulating the validity date Analytical study in light of the provisions of the Iraqi Consumer Protection Law No. (1) of 2010 - المدرس المساعد هاورى نورالدين صابر; األستاذ المساعد الدكتور مسعود حميد إسماعيل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The objective of this research is to understand the Consumer Protection Act (1) 2010 in establishing and upholding the rights of consumer’s goods and services. Ensuring a reasonable price is put in place without any fraudulent activities/results involved. In general, the protection of consumers rights is linked to guaranteeing a fair process of agreements and contracts between the consumer and other parties concerned. The protection of consumers right is therefore understood to be one of the main factors when considering the governments political movements. For this the Iraqi government adopted the Consumer Protection Act 2010 specifically to focus on the protection of the rights and duties of the consumer. This was believed to be a significant improvement for the life of Iraqi citizens/individuals. The Act contains crucial principles in protecting the rights of consumers, especially with the matter of prevention of fraudulently changing the expiry dates on goods. For this matter, this paper will closely analyze the protection provided by the act in relation to preventing the fraudulent activities in changing the expiry dates on the goods sold. The methodology of this research is entirely based on analysis of the Act and in detail examining the advantages and disadvantages of the Consumer Protection Act 2010. Moreover, to present recommendation in relation to further rights required in order to fully cover the protection of consumers in Iraq.